2021
DOI: 10.1364/oe.424886
|View full text |Cite
|
Sign up to set email alerts
|

Non-zero dispersion-shifted ring fiber for the orbital angular momentum mode

Abstract: As the dimension of orbital angular momentum (OAM) is orthogonal to the other degrees of freedom for photon, such as wavelength, it can be utilized to further increase data capacity in the wavelength division multiplexing (WDM) systems. However, the non-zero dispersion-shifted fiber (NZDSF) for the OAM mode has not yet been investigated or even proposed. In this work, we propose and design a ring fiber with low chromatic dispersion for the HE2,1 mode, which can serve as NZDSF for its corresponding OAM1,1 mode.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It is worth mentioning that this fiber has a central core, and a ring core surrounds it. It has been shown that fibers that have ring cores are sensitive to curvature perturbation [17]. Different lengths of NZ-DSF were tested, and we found experimentally that the 5 cm long sample showed the highest curvature sensitivity (−4.86 nm/m −1 from 1.25 to 1.77 m −1 ).…”
Section: Introductionmentioning
confidence: 74%
“…It is worth mentioning that this fiber has a central core, and a ring core surrounds it. It has been shown that fibers that have ring cores are sensitive to curvature perturbation [17]. Different lengths of NZ-DSF were tested, and we found experimentally that the 5 cm long sample showed the highest curvature sensitivity (−4.86 nm/m −1 from 1.25 to 1.77 m −1 ).…”
Section: Introductionmentioning
confidence: 74%